Copper-containing mesoporous bioactive glass nanoparticles as multifunctional agent for bone regeneration. (June 2017) - Bari, Alessandra; Bloise, Nora; Fiorilli, Sonia; Novajra, Giorgia; Vallet-Regí, Maria; Bruni, Giovanna; Torres-Pardo, Almudena; González-Calbet, José M.; Visai, Livia; Vitale-Brovarone, Chiara
Graphical abstract: Abstract: The application of mesoporous bioactive glasses (MBGs) containing controllable amount of different ions, with the aim to impart antibacterial activity, as well as stimulation of osteogenesis and angiogenesis, is attracting an increasing interest. In this contribution, in order to endow nano-sized MBG with additional biological functions, the framework of a binary SiO2 -CaO mesoporous glass was modified with different concentrations of copper ions (2 and 5% mol.), through a one-pot ultrasound-assisted sol-gel procedure. The Cu-containing MBG (2% mol.) showed high exposed surface area (550 m 2 g −1 ), uniform mesoporous channels (2.6 nm), remarkable in vitro bioactive behaviour and sustained release of Cu 2+ ions. Cu-MBG nanoparticles and their ionic dissolution extracts exhibited antibacterial effect against three different bacteria strains, E. coli, S. aureus, S. epidermidis, and the ability to inhibit and disperse the biofilm produced by S. epidermidis . The obtained results suggest that the developed material, which combines in single multifunctional agent excellent bioactivity and antimicrobial ability, offers promising opportunities for the prevention of infectious diseases and the effective treatment of bone defects. Statement of Significance: In order to endow mesoporous bioactive glass, characterized by excellent bioactive properties, with additional biological functions, Cu-doped mesoporous SiO2 -CaO glass (Cu-MBG) in the form of nanoparticles was prepared by an ultra-sound assisted one pot synthesis. The analysis of the bacterial viability, using different bacterial strains, and the morphological observation of the biofilm produced by the Staphylococcus epidermidis, revealed the antimicrobial effectiveness of the Cu-MBG and the relative ionic extracts against both the bacterial growth and the biofilm formation/dispersion, providing a true alternative to traditional antibiotic systemic therapies. The proposed multifunctional agent represents a promising and versatile platform for bone and soft tissues regeneration.